Penyuluhan Keamanan Pangan pada Ibu Rumah Tangga di RT 05 RW 06 Kelurahan Bandar Kidul Kota Kediri - Eka Desy Karismawati; Galuh Sitatorik; Nelli Nafidatul Isfanah; Anggraeta Ayu Fernanda; Arya Ulilalbab; Sony Andika Saputra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Two important factors in preventing foodborne illness are food hygiene and sanitation. These efforts can reduce the risk of bacterial contamination of food. Some examples of hazardous materials in food are plastics, metals, borax, formalin, insecticides, and banned food additives such as benzoic acid, ascorbic acid, lactic acid, and citric acid. The objective of this outreach is to increase knowledge about food safety and how to manage it. The method of counseling to the general public includes coordination with the head of the RT, providing materials, giving pre- and post-tests, and evaluating activities carried out at the RT head's house on June 1, 2024 at 16.00-17.30. The results of this activity were an increase in pre and post-test scores on questions regarding storage temperature and the main purpose of food storage, from 50 to 70 and 95 to 100. The conclusion of this counseling is that there is an increase in housewives' knowledge about food safety on a household scale. Suggestions for further counseling are to increase the number of targets so that more housewives understand the importance of household-scale food safety.